Economic evaluation methods used in home‐visiting interventions: A systematic search and review. (24th March 2021) - Bailey, Cate; Skouteris, Helen; Morris, Heather; O'Donnell, Renee; Hill, Briony; Ademi, Zanfina
Abstract: Home‐visiting interventions are used to improve outcomes for families experiencing disadvantage. As scarce resources must be allocated carefully, appropriate methods are required to provide accurate information on the effect of these programmes. We aimed to investigate: economic evaluation/analysis methods used in home‐visiting programmes for children, young people and families, study designs and methods suitable in situations where randomised‐controlled‐trials are not feasible, and type of costs included in analyses, including any implementation costs stated. A systematic search and review was conducted of existing full economic evaluation/analysis methods in home‐visiting programmes for children, young people and/or families. We included studies published in English between January 2000 and mid‐November 2020. Of the 4, 742 papers sourced, 60 were retained for full‐text review, and 21 included. Economic‐analysis methods found in the included studies were: within trial economic evaluation, economic evaluation using decision analytic modelling (i.e. cost‐utility, cost‐benefit analysis), cost comparison and cost‐consequence. Studies incorporating return on investment and budget impact analysis were also found. Study designs suitable when randomisation was not feasible included parallel cluster randomised trials and using pre‐post intervention data. Costs depended mainly on study context and only one study reported implementation costs. We hope this information will help guide future economic evaluations of home‐visiting interventions.